(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
In this article, the object of activity of food product examination is characterized mainly by four main indicators: assortment, quantity, quality and price indicators. The first three of these indicators satisfy specific human needs (physiological, sociological, psychological, etc.). Only through these classifications is information provided about the usefulness of the product for certain segments of consumers and its transformation into a commodity. The description of the product range includes information about the functional or social purpose of the product, based on a set of distinctive signs and types of groups.